Minimizando perdas e desperdício de hortifrutis em uma central de abastecimento de alimentos na cidade de Barbalha – CE: proposição de elementos norteadores - Lima, Márcia Maria Leite (Universidade do Vale do Rio dos Sinos, 2024)
Food losses and waste (PDA) have been one of the most discussed and emerging issues in the last 10 years. Both loss and waste are a serious global problem in ethical, social, environmental and economic contexts. Despite the availability of modern technologies and public policies to mitigate PDAs, it is estimated that 1.3 billion tons of food are lost or wasted each year, which represents 1/3 of all food produced worldwide. Given these perceptions, sustainable food production and consumption in Brazil face constant challenges, with a strong tendency to become serious problems in the future, due to food losses and waste. Traditional agricultural systems will face increasing challenges in maintaining and expanding their current levels of food production due to climate change, the intensive use of inputs and natural resources and, above all, changes in the eating habits of the Brazilian population. In Brazil, around 30% of the food produced is thrown away. This equates to around 46 million tonnes of food per year. The country is in 10th position among the countries that waste the most food in the world. More than R$1.3 billion in fruits and vegetables go to waste and each Brazilian discards an average of 60 kilos of good food per year. Parallel to this scenario, studies indicate that in 2030 the global population will be between 8.4 and 8.6 billion inhabitants, and in 2050, between 9.4 and 10.2 billion people. Given this scenario, the objective of this study was to propose a set of guiding elements for a CEASA unit located in a state in northeastern Brazil, aiming to mitigate food losses and waste in the fruit and vegetable sector. As a methodology, a case study was used, through a literature review, with a qualitative approach, of an exploratory nature. 30 permit holders, 1 (one) Ceasa manager and 1 (one) manager of the Mais Nutrição Program were surveyed in person with the help of a Google Forms form. Regarding the results obtained, the existence of losses and waste of fruit and vegetables in the processes between suppliers and CEASA distribution was identified. The factors related to PDAs are associated with the lack of sustainable strategic policies and guidelines on the part of CEASA, lack of management and defined processes of all actors involved in research, culture of waste and support from government entities and economic developers.
Keywords: Desenvolvimento sustentável; Perdas e desperdício de alimentos; Cadeia de abastecimento alimentar; CEASAS; Sustainable development; Food Loss and Waste; Food Supply Chain; ACCNPQ::Engenharias::Engenharia de Produção